Reaction selectivity in an ionized water dimer: nonadiabatic ab initio dynamics simulations - Svoboda, Ondřej; Hollas, Daniel; Ončák, Milan; Slavíček, Petr (Physical chemistry chemical physics, 2013)
We study dynamical processes following water dimer ionization. The nonadiabatic dynamical simulations of the water dimer radical cation are performed using a surface hopping technique and a Complete Active Space-Self Consistent Field (CASSCF) method for the description of electronic structure. The main goal of this study is to find out whether a state-dependent reactivity is observed for the water dimer radical cation. We provide a detailed mapping of the potential energy surfaces (PESs) in the relevant coordinates for different electronic states. Dynamical patterns are discussed on the basis of static PES cuts and available experimental data. As a product of the reaction, we observed either proton transferred structure (H3O(+)···OH˙) or various dissociated structures (H3O(+) + OH˙, H2O˙(+) + H2O, H˙ + OH˙ + H2O˙(+)). The relative yields are controlled by the populated electronic state of the radical cation. The proton transfer upon the HOMO electron ionization is an ultrafast process, taking less than 100 fs, in cases of higher energy ionization the dynamical processes occur on longer timescales (200-300 fs). We also discuss the implications of our simulations for the efficiency of the recently identified intermolecular coulomb decay (ICD) process in the water dimer.
Keywords: Molecular Dynamics Simulation; voda; Dimerization; Water; simulace molekulární dynamiky; dimerizace